Frontier and hotspots in the role of sentinel lymph node in endometrial cancer based on bibliometric analysis - Li, Di-Ying; Yang, Yi; Xie, Hai-Hui; Shao, Yin; Fang, Su; Zhang, Jin-Ling (Frontiers in Oncology, 2025)
The role of sentinel lymph nodes (SLN) in endometrial cancer remains controversial. Our study is dedicated to employing bibliometric methods to explore the correlation between endometrial cancer and SLN. We aim to statistically analyze the existing literature on sentinel lymph nodes in the field of endometrial cancer research and explore future research trends and hotspots. Global literature on the role of SLN in endometrial cancer published from 1900 to the present in the Web of Science core database was searched. Cited articles were focused on by extracting information such as country, journal, keywords, institution and author. Descriptive statistics and visual analysis were performed using VOSviewer and R package. A total of 545 articles were screened, most of which were from USA (159 articles). Based on Bradford Law, Gynecologic Oncology and International Journal of Gynecological Cancer were core journals in this research field. Abu-Rustum Nadeem R from Mem Sloan Kettering Cancer Center was most productive author. The current research focus was endometrial cancer, SLN, lymphadenectomy, biopsy, indocyanine green (ICG). The complication, guidelines, outcomes and survival were the frontier of current research. Researchers in different countries have paid extensive attention to the role of SLN in the treatment of endometrial cancer, and have made breakthroughs in this field. SLN mapping has a promising prospect for the recurrence and prognosis of patients with endometrial cancer. More clinical research is needed to discover the role of SLN in the future.